Iron-catalyzed alkyne alkylzincation affected by counterions - Lu-Jie Li; Qiao Zhang; Peng He; Ming-Yao Huang; Shou-Fei Zhu (Nature Communications)
Abstract Metal complex catalysts typically comprise three components: ligands, central metals, and counterions. The counterion profoundly influences the activity and selectivity of numerous catalytic reactions, while such a phenomenon is rarely observed in carbozincation reactions. Herein, we discover that the catalytic efficiency of iron-catalyzed alkylzincation of alkynes is markedly enhanced when the weakly coordinating bulky counterion tetrakis(3,5-bis(trifluoromethyl)phenyl)borate ([BArF 4]−) is incorporated into the reaction. This approach yields ionic iron catalysts with exceptional activity (up to 32,900 TON), regioselectivity (mostly >95:5), and stereoselectivity (mostly >95:5) in both alkylzincation reactions of terminal and internal alkynes. Notably, the methylzincation of non-activated terminal and internal alkynes is rendered feasible. This methodology also enables the efficient synthesis of a diverse array of biologically active molecules and their key intermediates. Mechanistic investigations suggest that a cationic Fe(II) species serves as the active catalytic species and the weakly coordinating bulky counterion stabilizes a cationic iron(II) alkyl complex without competing with the alkyne substrate.